Ruptured Liver Abscess in Neonates: Report of Two Cases - Niyaz Ahmed Khan; SR Choudhury; Praveen Jhanwar (EL-Med-Pub, 2016)
Neonatal hepatic abscess is a rare disease seen mainly in preterm following umbilical catheterisation. Liver abscess in term neonates without any predisposing factor is still rarer and only few cases have been reported in the literature. Here we report two cases of liver abscess in term neonates presenting with abdominal mass due to rupture.